AI-Enabled Cloud Orchestration for Automated Workflows: A Paradigm Shift in Enterprise IT Operations - Tarun Kumar Chatterjee (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
AI-enabled cloud orchestration represents a fundamental paradigm shift in enterprise IT operations, transforming traditional reactive management into proactive, self-optimizing environments. The integration of artificial intelligence with cloud infrastructure enables organizations to predict workloads, optimize resource allocation, and automate complex tasks across distributed computing environments. This technological evolution addresses the increasing complexity of enterprise workflows where manual intervention becomes impractical due to scale and intricacy. As digital transformation accelerates across industries, AI-enabled orchestration provides the intelligence required to enhance service delivery, reduce operational overhead, and achieve continuous optimization. The progression from manual configuration to sophisticated AI-driven systems marks a transition that delivers measurable advantages in resource utilization, incident prevention, and business agility. Through dynamic resource optimization, intelligent workload placement, and automated incident response, organizations can rapidly adapt to changing environments while minimizing operational costs capabilities that prove crucial for enterprise modernization in an increasingly competitive digital landscape.